1986
DOI: 10.1128/iai.54.1.96-103.1986
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of rat Pneumocystis carinii antigens recognized by human and rat antibodies by using western immunoblotting

Abstract: The major Pneumocystis carinii antigens inducing antibody responses in infected hosts were identified by Western immunoblotting techniques. The biochemical nature of these antigens was also elucidated. Sodium dodecyl sulfate-polyacrylamide gel electrophoresis followed by protein staining revealed a major component with a molecular weight (MW) of greater than 205,000. This major component disappeared and a new major protein staining component of approximately 110,00 to 116,000 MW appeared when electrophoresis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
31
0

Year Published

1987
1987
1997
1997

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(34 citation statements)
references
References 13 publications
3
31
0
Order By: Relevance
“…We found that the epitopes recognized by SMoAb had a similar ultrastructural localization in organisms of human and rat origin, whereas the epitopes recognized by DMoAb were present only in organisms of human origin. This is consistent with previous observations suggesting the existence of both strainspecific and shared antigens in PC from different hosts (Gigliotti et al 1986;Graves et al 1986b;Kovacs et al 1989;Lundgren et a/. 1991;Gigliotti 1992).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We found that the epitopes recognized by SMoAb had a similar ultrastructural localization in organisms of human and rat origin, whereas the epitopes recognized by DMoAb were present only in organisms of human origin. This is consistent with previous observations suggesting the existence of both strainspecific and shared antigens in PC from different hosts (Gigliotti et al 1986;Graves et al 1986b;Kovacs et al 1989;Lundgren et a/. 1991;Gigliotti 1992).…”
Section: Discussionsupporting
confidence: 93%
“…Several research groups have produced monoclonal antibodies against PC, both for diagnostic and research purposes (Gigliotti et al 1986;Gigliotti et al 1988; Graves et al 1986a;Linder et al 1987; Magee et al 1991;Gigliotti 1992). Studies using these antibodies have shown that PC isolates from different hosts are antigenically dissimilar, although they share some common antigens (Graves et al 1986b;Kovacs et al 1989;Lundgren et al 199 1 ;Bauer et al 1993;Gigliotti et al 1993a). There is evidence of host speciesspecific genotypic variations (Sinclair et al 1991;Edlind et al 1992).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Regardless of the host species from which they are obtained, P. c. carinii are covered by a large (90-120 kDa) glycoprotein called either major surface glycoprotein (MSG) Kovacs et al, 1988;Linke et al, 1989;Wada et al, 1993;Sunkin et al, 1994) or gpA (Haidaris et al, 1992;Wright et al, 1994). MSG is thought to play a crucial role in host-pathogen interactions because it is recognized by serum antibodies and T cells from exposed hosts (Graves et al, 1986;Gigliotti et al, 1988;Kovacs et al, 1988;Linke et al, 1989;Nakamura et al, 1989;Fisher et al, 1991;Lundgren et al, 1992;Smulian et al, 1993a;Garbe and Stringer, 1994), and binds to fibronectin (Pottratz and Martin, 1990), Surfactant Protein A (Zimmerman et al, 1992), and other host proteins (Ezekowitz et al, 1991;Limper et al, 1991;1993;Neese et al, 1994). Each P. c. carinii cell has the potential to express numerous different MSG isoforms because the genome of P. c. carinii encodes about 100 different MSG genes, distributed among all of the 15 discernible chromosomes (Kovacs et al, 1993;Wada et al, 1993;Sunkin et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Crossed affinoimmunoelectrophoresis is a technique that can be used to examine the possibility of carbohydrate-dependent microheterogeneity (7). With the human and the rat P carinii surface antigens being different both in their glycosylation and antigenicity (6,10,14,25), we undertook this study to further characterize the glycosylation of the major human Z? carinii glycoprotein Gp 95.…”
mentioning
confidence: 99%